Super Fancy Company: Fancy Remote / Nur Sahira Ibharim - Ibharim, Nur Sahira (2020)
At present, the rising of the problems can be solved through the invention of the new product. The launching of our products is due to the problems that have been analysed such as having problems with internet connections to use the printers which can bring burdens towards them. The new product to be launch has undergone several processes such as analyse the product. Then, it proceeded to design the products and features including technology used for product development. The prototype is designed and created based on design and development. The target market has been analysed for three years and fortunately, it gives good results. This may be due to the functions of our product that cannot be found in our competitors, which means that our product has more competitive advantages from our competitors. As our sales keep going increased year by year, the profit also increased. Lots of techniques and strategies were used to make the new product being accepted to the community including promotion strategy. Since this need lots of help, the management team has been assigned to their tasks and responsibilities